Investigation of the strength property of 3D printed products in bending deformation to optimize material distribution - A. V. Shimokhin; A. N. Sorokin; S. N. Boltovsky; V. N. Kuznetsova; I. S. Kuznetsov (Омский научный вестник)
The article considers a method of optimal material distribution inside a 3D printed sample. Several variants of material distribution are considered, including the beam shape of equal resistance while retaining the outer frame of the specimen as a rectangular parallelepiped with a square cross-section. The manufactured samples are subjected to destruction during static bending testing. The results show the reduction of used material by 30 % and preservation of specimen strength properties with 100 % material filling. Moreover, experimental results are presented and research issues for further investigations are highlighted.